Agile innovation : the revolutionary approach to accelerate success, inspire engagement and ignite creativity - Morris, Langdon; Ma, Moses, 1956-; Wu, Po Chi, 1948- (2014)
'Effective innovation doesn't happen by accident - it happens by design! Agile Innovation is the field guide to designing and implementing effective innovation methods and projects, and facilitating collaborative processes that enable people to solve complex problems and create breakthrough solutions. The book offers a comprehensive Innovation Master Plan Framework, which provides five critical performance areas and how to optimize them for sustained innovation improvement. Agile Innovation teaches how to discover and develop better ideas, learn and work together more profitably and effectively, and create breakthroughs'--
Includes index.
Keywords: Organizational change; Creative ability in business; Success in business; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management